Acute graft thrombosis in patients who underwent renal transplant and received anticoagulant or antiplatelet agents. A systematic review and meta-analysis - Guerra, Rodrigo [UNESP]; Kawano, Paulo Roberto [UNESP]; Amaro, Marcelo Petean; Yamamoto, Hamilto Akihissa [UNESP]; Gomes Filho, Fernando Ferreira [UNESP]; Amaro, Joao Luiz [UNESP]; El Dibl, Regina Paolucci [UNESP]; Garcia-Perdomo, Herney Andres; Reis, Leonardo Oliveira (E-century Publishing Corp, 2022)
Objectives: Thrombosis is a major cause of early allograft loss in renal transplantation. Herein, we assessed the frequency of acute graft thrombosis in patients who underwent renal transplant and received anticoagulant or antiplatelet agents. Methods: We performed a systematic review of all available case series studies of anticoagulant and/or antiplatelet prophylaxis of thrombosis in renal transplantation. The data were pooled in a proportional meta-analysis. Results: Twenty-one case series were identified from 7,160 retrieved titles. A total of 3,246 patients were analyzed (1,718 treated with antiplatelet and/or anticoagulant agents and 1,528 non-treated control subjects). Allograft thrombosis occurred in 7.24% (95% CI 3.45 to 12.27%) of the patients receiving no intervention compared with 3.38% (95% CI 1.45 to 6.1%), 1.2% (95% CI 0.6 to 2.1%) and 0.47% (95% CI 0.001 to 1.79%) of the patients in the anticoagulant, aspirin, and aspirin + anticoagulant groups, respectively. The bleeding complication rate for anticoagulants was significantly higher than in the other groups. Conclusions: Our data suggests that anticoagulants, and aspirin, either alone or in association with an anticoagulant, seem to have a low frequency of acute allograft thrombosis after kidney transplantation. Higher hemorrhagic complication rates might occur when anticoagulants are used.
Keywords: Anticoagulants; Aspirin; Kidney transplantation; Meta-analysis; Thrombosis